Optimization of Biosorbent on Cd(II) Metal Biosorption Using Duck Eggshell Waste - Tasmalia, Ria; Prameswari, Nida Hamidah; Paramita, Vita (Vocational College of Universitas Diponegoro, 2022)
Every year the production of duck eggs in Indonesia has increased, this case leads to an increase in the waste of duck eggshells. Duck eggshell waste has components that can be utilized into a biosorbent. To improve the quality of the biosorbent, can be done with an activation method and immobilization method. The purpose of this study was to determine the effectiveness of biosorbents made from duck eggshell waste in absorbing Cd(II) metal. In this study, duck eggshells were activated with physical activation by heating in a furnace at a temperature of 900oC for 2 hours. Independent variables of this study are biosorbent mass, contact time and concentration of cadmium solution. Critical values for Cd levels optimization conditions are accomplished when the biosorbent mass 1.45 grams, contact time 100 minutes and Cd solution concentration 86 ppm with a percentage decrease in Cd levels in the amount of 89%.